Tuning 2D MXenes by Surface Controlling and Interlayer Engineering: Methods, Properties, and Synchrotron Radiation Characterizations - Wang, Changda; Chen, Shuangming; Song, Li (Advanced functional materials, 2020)
MXenes, layered transition metal carbides/nitrides, have already received considerable attention in various research areas including but not limited to energy storage/conversion and photo/electrocatalysis. In fact, the intrinsic property of MXenes is highly tunable by controlling the surface terminations and interlayer spacing. Moreover, synchrotron radiation X‐ray characterizations have shown high potential for exploring the causal relationship between the properties and structure of MXenes. Particularly, operando X‐ray measurements could provide useful insight for better understanding the dynamic process of MXene‐based energy materials. In this review, a comprehensive summary of recent studies on surface controlling, interlayer engineering, and the synchrotron‐based characterizations of MXenes is presented. The outlook of MXenes and applications of advanced X‐ray characterizations are also discussed. In this review, the structure and synthesis strategies of MXenes are briefly discussed. Surface controlling, interlayer engineering toward the tunable structure of MXenes, and relevant applications are also comprehensively summarized. Particularly, the progresses and advantages of synchrotron‐based characterizations in the exploration of MXenes' structure and dynamic mechanism are emphasized, and the challenges and prospects are proposed as well.